3 Treatment response in cardiac al amyloidosis assessed by CMR: findings at 3 months, 6 months and 1 year post-chemotherapy. (May 2018) - Martinez-Naharro, Ana; Kotecha, Tushar; Baggiano, Andrea; Boldrini, Michele; Rezk, Tamer; Francis, Rohin; Fayed, Hossam; Knight, Dan; Moon, James; Kellman, Peter; Gillmore, Julian; Hawkins, Philip; et al.
Abstract : Introduction: Cardiac involvement in immunoglobulin light chain (AL) amyloidosis is the major determinant of survival. Cardiac response to chemotherapy is conventionally assessed by serum brain natriuretic peptide (NT-proBNP) and echocardiography, but neither quantify amyloid burden. The aim of this study was to evaluate cardiac AL amyloid by CMR at 3 months, 6 months and 1 year post-chemotherapy. Methods: 78 patients with cardiac AL amyloidosis were studied serially using CMR with T1 mapping and extracellular volume at baseline and 3 months, 6 months and 12 months post-chemotherapy. Results: At 6 months, 60% of patients achieved a complete or very good partial haematological response, and 40% patients a partial response or no response. Amyloid regression was not detectable, however, amyloid progression was detectable in 30% patients at 6 months. Although this occurred in the PR group, it also occurred in the CR and VGPR groups (47%). At one year, 66% patients achieved a CR or VGPR. Regression of amyloid was seen in 32% patients, all with CR or VGPR and 0 patients in PR or NR (p<0.05). 46% patients with changes in ECV consistent with regression of amyloid had changes in LGE. Amyloid regression was associated with significant reduction in LV mass and increased LVEDV (p<0.05). Conclusion: In newly diagnosed and treated AL amyloidosis, CMR demonstrates the dynamic biology of infiltration: increasing rapidly, particularly if chemotherapy fails to switch off light chain production; regressing more slowly (by 1 year) if effective. Serial monitoring of myocardial infiltration has the potential for new AL amyloidosis therapeutic regimes based on myocardial organ response.